A horse or a zebra? Unusual manifestations of common cutaneous infections in primary immunodeficiency pediatric patients - Ollech, Ayelet; Simon, Amos J; Lev, Atar; Stauber, Tali; Sherman, Gilad; Solomon, Michal; Barzilai, Aviv; Somech, Raz; Greenberger, Shoshana (Frontiers in Pediatrics, 2023)
Abstract: Background: Patients with primary immunodeficiency disorders (PID)s often suffer from recurrent infections, due to their inappropriate immune response to both common and less common pathogens. These patients may present with unique and severe cutaneous infectious manifestations that are not common in healthy individuals and may be more challenging to diagnose and treat. Objective: To describe a cohort of patients with PIDs with atypical presentations of skin infections who posed a diagnostic and/or therapeutic challenge. Methods: A retrospective study of pediatric patients with PID with atypical presentations of infections treated at the immunodeficiency specialty clinic and the pediatric dermatology clinic in Sheba Medical Center between September 2012 and August 2022. The epidemiologic data, PID diagnosis, infectious etiology, presentation, course, and treatment were recorded. Results: Eight children with a diagnosis of PID were included, five of whom were boys. The average age at PID diagnosis was 1.7(±SD 3.2) years. The average age of cutaneous infection was 6.9 (±SD 5.9) years. Three patients were born to consanguineous parents. The PIDs included: Common variable immunodeficiency, Severe combined immunodeficiency, Dock8 deficiency, Ataxia telangiectasia, CARD-11 deficiency, MALT-1 deficiency, chronic granulomatous disease, and a combined cellular and humoral immunodeficiency syndrome of unknown etiology. The infections included: ulcerative -hemorrhagic varicella-zoster virus (2 cases) atypical fungal and bacterial infections, resistant Norwegian scabies, giant perianal verrucae (2 cases), and diffuse molluscum contagiosum. Conclusions: In this case series we present unusual manifestations of infectious skin diseases in pediatric patients with PID. In some of the cases, recognition of the infectious process prompted life-saving treatment. Increasing familiarity with these dermatological manifestations as well as keeping a high index of suspicion are important to enable early diagnosis of cutaneous infections in PIDs and initiation of prompt suitable treatment.